Evaluation of Interval Times from Onset to Reperfusion in Patients Undergoing Endovascular Therapy in the IMS III Trial - Goyal, Mayank (2014)
BACKGROUND: Meaningful delays occurred in the IMS III trial. Analysis of the workflow will identify factors contributing to the in-hospital delays. METHODS AND RESULTS: In the endovascular arm of the IMS III trial, these time intervals were calculated: stroke onset to ED arrival; ED to CT; CT to IV tPA start; IV tPA start to randomization; randomization to groin puncture; groin puncture to thrombus identification; thrombus identification to start of endovascular therapy; start of endovascular therapy to reperfusion. The effects of enrollment time, CTA use, inter-hospital transfers, and intubation on workflow were evaluated. Delays notably occurred in the time intervals from IV tPA initiation to groin puncture (median 84 minutes) and start of endovascular therapy to reperfusion (median 85 minutes). The CT to groin puncture time was significantly shorter during working hours than after. Times from ED to reperfusion and groin puncture to reperfusion decreased over the trial period. Patients with CTA had shorter ED to reperfusion and onset to reperfusion times. Transfer of patients resulted in a longer onset to reperfusion time compared to those treated in the same center. Age, sex, NIHSS, and intubation did not impact delays. CONCLUSIONS: Important delays were identified prior to reperfusion in the IMS III trial. Delays decreased as the trial progressed. Use of CTA and endovascular treatment in the same center were associated with time savings. These data may help in optimizing workflow in current and future endovascular trials. CLINICAL TRIAL REGISTRATION INFORMATION: http://clinicaltrials.gov. Identifier: NCT00359424.